2016
DOI: 10.1016/j.labeco.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance as a productive factor

Abstract: In this paper, we present a less-explored channel through which health insurance impacts productivity: by o¤ering health insurance, employers reduce the expected time workers spend out of work in sick days. Using data from the Medical Expenditure Panel Survey (MEPS), we show that a worker with health coverage misses on average 52% fewer workdays than uninsured workers, after controlling for endogeneity. We develop a model that embodies this impact of health coverage in productivity. In our model, health insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 31 publications
(34 reference statements)
0
19
0
Order By: Relevance
“…The most direct explanation is that health insurance limits negative earning shocks by improving worker health and, in turn, the quantity, quality, and reliability of labor output. The literature strongly supports the hypothesis that better perceptions of one's physical and mental health can translate into increased labor supply (Frijters, Johnston, and Shields, 2014;Bubonya, Cobb-Clark, and Wooden, 2017;Dizioli and Pinheiro, 2016). Perceptions of one's health are likely influenced by insurance status.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The most direct explanation is that health insurance limits negative earning shocks by improving worker health and, in turn, the quantity, quality, and reliability of labor output. The literature strongly supports the hypothesis that better perceptions of one's physical and mental health can translate into increased labor supply (Frijters, Johnston, and Shields, 2014;Bubonya, Cobb-Clark, and Wooden, 2017;Dizioli and Pinheiro, 2016). Perceptions of one's health are likely influenced by insurance status.…”
Section: Introductionmentioning
confidence: 61%
“…These researchers do not, however, explore the role of health insurance on earnings streams after a health event nor do they use a framework in which insurance is quasirandomized. One possible exception is Dizioli and Pinheiro (2016). Using U.S. Census region of residence as instrument variables for the probability of holding health insurance coverage, these authors find that workers with health insurance missed 76% fewer workdays than comparable workers without health insurance.…”
Section: Literaturementioning
confidence: 99%
“…Much can be done on this front. For example, firms could consider implementing structured wellness programs and providing higher quality health insurance to their employees in order to enhance their employees' productivity and reduce sickness absenteeism (Dizioli and Pinheiro 2016;Gubler, Larkin, and Pierce 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In another instance, researchers such as Fairlie (14) and Bauer and Sinning (15) further, extended this method to the non-linear regression model to demonstrate the impact of health insurance on the economy. Moreover, research conducted by Dizioli and Pinheiro (16) showed that the rural medical insurance system can significantly increase the agricultural labor hours of rural residents and, at the same time, improve the labor supply and supply efficiency of the rural residents (17).…”
Section: Introductionmentioning
confidence: 99%